Ectopic varices (a rare cause of stoma bleed) - Kabir, Syed A.; Kabir, Syed I.; Pillai, S.; Chakrabarti, M. (International Surgery Journal, 2016)
Hemorrhage from stoma due to ectopic varices is a rare condition, which can be seen in patients due to portal hypertension of any cause. Resnick et al. were the first to describe in the year 1968. Unfortunately, there has been no randomized controlled trials to formally assess the best management approach for such a condition, and conservative methods are temporary as they re-bleed within 1 year time. Definitive treatment requires a multidisciplinary team approach as they have a high mortality and morbidity rate. The treatment is aimed at reducing the portal-hypertension, which can be achieved with porto-systemic shunts.